2021
DOI: 10.1590/1806-9061-2020-1298
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms of Candidate Genes Related to Egg Production Traits in Vietnamese Indigenous Chickens

Abstract: Vinh NT I https://orcid.org/0000-0003-4881-7506The objective of this work was to detect single nucleotide polymorphisms (SNPs) in two candidate genes known to relate with reproductive traits in Vietnamese chicken. Two indigenous breeds Ri and Mia chickens were used for genotyping 4 SNPs namely intron 1 of growth hormon gene (GH), exon 5 of prolactin receptor gene (PRLR5), a 24 bp nucleotide sequence insertion-deletion at situation -358 in 5'untranslated region of prolatin gene (PRL24); and at site C2404T of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Bruders et al, 2020;Domyan et al, 2014;Han et al, 2011;Krishnan & Cryberg, 2019;Krishnan, 2019;Maclary et al, 2023; , 2022). There are many studies, mostly in chickens, that show associations between SVs and feathering phenotypes (Chen, Xi, et al, 2022;Derks et al, 2018;Domyan et al, 2016;Dong et al, 2018;Elferink et al, 2008;Li et al, 2020;Li, Lee, et al, 2021;Mou et al, 2011;Ng et al, 2012;Shen et al, 2023); comb, muff and beard traits (Dorshorst et al, 2015;Guo et al, 2016;Imsland et al, 2012;Moro et al, 2015;Sato et al, 2010;Wang et al, 2017;Wright et al, 2009;Yang et al, 2020Yang et al, , 2021; and egg production (Cui et al, 2006;Huang et al, 2018;Lan et al, 2021;Manoharan et al, 2021;Vinh et al, 2021). Although less common, there are also associations between SVs and behaviour and domestication (Abe et al, 2013;Chen, Bai, et al, 2022;Falker-Gieske et al, 2023;Khatri et al, 2019;Komiyama et al, 2014;Krause et al, 2019;Rubin et al, 2010;Seol et al, 2019;Zhou et al, 2018;…”
Section: Identif Ying a Ssociations B E T Ween S Vs And Phenot Ypi C ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Bruders et al, 2020;Domyan et al, 2014;Han et al, 2011;Krishnan & Cryberg, 2019;Krishnan, 2019;Maclary et al, 2023; , 2022). There are many studies, mostly in chickens, that show associations between SVs and feathering phenotypes (Chen, Xi, et al, 2022;Derks et al, 2018;Domyan et al, 2016;Dong et al, 2018;Elferink et al, 2008;Li et al, 2020;Li, Lee, et al, 2021;Mou et al, 2011;Ng et al, 2012;Shen et al, 2023); comb, muff and beard traits (Dorshorst et al, 2015;Guo et al, 2016;Imsland et al, 2012;Moro et al, 2015;Sato et al, 2010;Wang et al, 2017;Wright et al, 2009;Yang et al, 2020Yang et al, , 2021; and egg production (Cui et al, 2006;Huang et al, 2018;Lan et al, 2021;Manoharan et al, 2021;Vinh et al, 2021). Although less common, there are also associations between SVs and behaviour and domestication (Abe et al, 2013;Chen, Bai, et al, 2022;Falker-Gieske et al, 2023;Khatri et al, 2019;Komiyama et al, 2014;Krause et al, 2019;Rubin et al, 2010;Seol et al, 2019;Zhou et al, 2018;…”
Section: Identif Ying a Ssociations B E T Ween S Vs And Phenot Ypi C ...mentioning
confidence: 99%
“…SVs (Box 1), which include insertions, deletions, inversions and duplications, traditionally describe genomic alterations involving DNA regions longer than 50 bp (Bickhart & Liu, 2014). However, SVs shorter than 50 bp can still have significant impact on phenotypes, for instance they underlie plumage colouration in Japanese Quail (Hiragaki et al., 2008; Minvielle et al., 2010) and chickens (Adetula et al., 2020), as well as impacting egg production in both species (Lan et al., 2021; Manoharan et al., 2021; Vinh et al., 2021). Additionally, transposable elements (TEs), which encompass various classes of mobile genetic elements, can be considered a form of SV (see below).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported a significantly positive association between the 24 bp indel polymorphism and egg production (Cui et al, 2006;Begli et al, 2010;Rashidi et al, 2012;Sarvestani et al, 2013;Manoharan et al, 2021;Tu et al, 2023), while other studies showed no positive association (Lotfi et al, 2013;Chaovapasee et al, 2020). In Vietnam, several reports have been done on the PRL/24 indel polymorphism in Lien Minh, Ri, Mia and Silke chickens (Nguyen et al, 2018;Vinh et al, 2021;Tu et al, 2023) but have no data on VLV chicken breed, upto date. Therefore, this research aimed to investigate the polymorphism of the 24 bp in/del of the PRL gene in the promoter region, as well as to determine the effect of polymorphism on some reproductive traits of VLV dualpurpose color chickens.…”
Section: Introductionmentioning
confidence: 99%
“…PCR-RFLP is a popular, reliable and cost-effective technique for identifying targeted single nucleotide polymorphisms (SNPs) (Narayanan, 1991). The recent advancement in nextgeneration sequencing and genotyping technologies is used for the identification of SNPs related to production (Vinh et al, 2021).The avian egg-production process is mainly in control of the hypothalamic-pituitary-gonadal axis (Kuo et al, 2005). A neuropeptide Y (NPY) is investigated routinely to decode its role in the hypothalamus regulation of…”
mentioning
confidence: 99%
“…PCR-RFLP is a popular, reliable and cost-effective technique for identifying targeted single nucleotide polymorphisms (SNPs) (Narayanan, 1991). The recent advancement in nextgeneration sequencing and genotyping technologies is used for the identification of SNPs related to production (Vinh et al, 2021).…”
mentioning
confidence: 99%